Nutrition, Gut Microbiota, and Alzheimer's Disease - Romanenko, Mariana; Kholin, Victor; Koliada, Alexander; Vaiserman, Alexander (Frontiers in Psychiatry, 2021)
Nutrition is known to play an important role in the pathogenesis of Alzheimer’s disease. Evidence is obtained that the gut microbiota is a key player in these processes. Dietary changes (both adverse and beneficial) may influence the microbiome composition, thereby affecting the gut-brain axis and the subsequent risk for Alzheimer’s disease progression. In this review, the research findings that support the role of intestinal microbiota in connection between nutritional factors and the risk for Alzheimer’s disease onset and progression are summarized. The mechanisms potentially involved in these processes as well as the potential of probiotics and prebiotics in therapeutic modulation of contributed pathways are discussed.